IMPROVEMENT OF THE HYDRAULIC EXCAVATOR BUCKET DESIGN - G. G. Buriy; V. S. Shherbakov; S. B. Skobelev; V. F. Kovalevskiy (Вестник СибАДИ)
Introduction. Construction of engineering structures is impossible without building and road machines. The large volume of financing is allocated for such machines’ purchase. The main ways of reducing costs of the equipment consist in more rational operation of the equipment and also in decrease of equipment’s cost by constructive changes. The paper demonstrates the new design of the single-bucket hydraulic excavator with smaller cost.Materials and methods. The main ways of cost reduction for construction machines are more rational operation and depreciation of a design with the required characteristics’ maintaining. The paper describes constructive changes of the working equipment of the single-bucket hydraulic excavator, which allow decreasing the production costs.Results. The authors describe the new bucket design of the single-bucket hydraulic excavator. Moreover, the authors carry out the analysis of the existing buckets’ design. The paper also illustrates the functioning on bucket forces while digging process. The authors describe the solutions of the problem for productivity increase of the single-bucket in hydraulic excavators. In addition, the authors make the scheme of the bucket loading while digging process. Such scheme helps to reduce resistance forces of digging.Discussion and conclusions. As a result, the paper presents the design of the working equipment of the hydraulic excavator’s single-bucket, which allows reducing resistance forces of digging. Such results would help to establish buckets of bigger capacity and would lead to the productivity increase.